Efektivitas Pendekatan Culturally Responsive Teaching (CRT) Untuk Meningkatkan Hasil Belajar Siswa Kelas II Sekolah Dasar - Khasanah, Indah Milati (Alifbata : Jurnal Pendidikan Dasar, 2023)
The purpose this research is to improve student learning outcomes the theme togetherness in the school environment. This research is quantitative study conducted in two hours study and takes pretest and posttest data. The research sample is class II with learning outcomes. The data obtained from the research are the learning outcomes the cognitive, affective, and psychomotor aspects and the results the research show that from the pretest and posttest the learning outcomes in these three aspects. The learning outcomes the pretest and posttest cognitive aspects that the researchers carried out in class II students Elementary School after being analyzed by researchers through the normality gain according to Meltzer resulted in the "High" criterion. Based on the results the study, can be concluded that the use culture in the form special food from students' backgrounds learning medium can improve student learning outcomes on ttheme togetherness in the school environment.